Pluralism and Religious Conflict in the Frame of Regional Autonomy in West Sumatra - Nunu Burhanuddin; Dodi Pasilaputra; Hardi Putra Wirman (ADDIN, 2020)
The diversity of ethnicities, races, and religions is a reality in the life of the nation and state, although it is undeniable that there is a potential for conflict. This study aimed to explain the pattern of religious harmony in West Sumatra within the framework of regional autonomy which is adopted from the cultural system and local wisdom. This study used a phenomenological approach to provide accurate conditions of multi-ethnic, cultural, and religious communities. The results showed that the pattern of religious harmony through the resolution of religious conflicts in several regions in West Sumatra was carried out through the alignment of regional autonomy with local customs and culture. Forms of alignment include alignment of school uniforms, equal distribution of sacrificial meat, the presence of baralek, the tradition of manyiriah, interfaith graves between Muslims and Christians, and the application of customary philosophies. This study contributes to the theory of a cultural approach based on local wisdom in resolving religious conflicts and strengthening social integration of the community.